Job Loss and Immigrant Labor Market Performance - Bernt Bratsberg; Oddbjørn Raaum; Knut Røed (Institute for the Study of Labor (IZA), 2016)
While integration policies typically focus on labor market entry, we present evidence showing that immigrants from low-income countries tend to have more precarious jobs, and face more severe consequences of job loss, than natives. For immigrant workers in the Norwegian private sector, the probability of job loss in the near future is twice that of native workers. Using corporate bankruptcy for identification, we find that the adverse effects of job loss on future employment and earnings are more than twice as large for immigrant employees.
Keywords: F22; H55; J24; J65; 330; migration; job loss; firm closure; unemployment